Complexes of Cu(II) and Ni(II) Sulphate with Acetone and Acetaldehyde Hydrazones Derived from Valeric Acid and Isovaleric Acid - Aliyu, H.D.; Ojo, A.S. (Asian Journal of Chemistry, 2011)
Eight complexes of Ni(II) and Cu(II) sulphates with valeric acid and isovaleric acid hydrazones of acetone and acetaldehyde were synthesized and characterized. The hydrazones act as a bidentate ligands coordinating through the oxygen of the carbonyl and the azomethine nitrogen, while the SO42– ions occurs in the outer sphere complex. The microbial activities of the ligands and their metal complexes are encouraging.